Christianity: A Social and Cultural History - Kee H. C.; Kee Howard Clark; Albu Emily; Lindberg Carter; Frost J. William; Robert Dana L. (Upper Saddle River Prentice-Hall, Inc., 1998)
Written by contributing scholars who are experts in specific facets of developing Christianity, this survey provides a well-rounded introduction to the history of Christianity and is ideal for anyone interested in the impact of Christianity of world culture down through history. It shows how Christianity emerged from its original Jewish context and developed into a worldwide religion, offering perceptive studies on how its origins and development were influenced by the changing social and cultural contexts in which the founders and leaders of this tradition lived and thought. Provides detailed evidence of the influence of Greco-Roman and Jewish religious concepts and religious movements on the origins of Christianity, considers the structuring of the church conceptually and organizationally in Europe, and discusses Christianity's spread and growth in America and throughout the world. Looks at the profound impact of the culture of the later Roman and medieval world on the development of Christian doctrine and intellectual traditions and helps readers understand the reasons for the divisions between Catholic and Protestant traditions. For theologians.
Keywords: 27 (NhRISTIQNSTWOs